Rekonstruksi Rekrutmen Dan Pengawasan Eksternal Hakim Mahkamah Konstitusi Dengan Pendekatan Hukum Progresif - Fauzanto, Adi (Jurnal Panorama Hukum, 2020)
Indonesia is a country of law. Jimly Asshiddiqie formulated twelve main principles of modern rule of law, one of which was the existence of a free and impartial judiciary, and the existence of a constitutional justice mechanism. After amendments of the constitution of the 1945 Constitution of the Republic of Indonesia, it has implications for the structure of more democratic state institutions. These changes give birth to the building of state relief from one another in an equal position with mutual control (checks and balances). Judicial Power is an independent power to administer justice to uphold law and justice. An independent judicial power or what is referred to as the principle of independence cannot be separated from the principle of checks and balances adopted by Indonesia to ensure that the institutions of authority and duties are balanced and the principles of the state are based on law and constitution. In Indonesia, the Constitutional Court judiciary was born on August 13, 2003, which was formed based on Law Number 24 of 2003 concerning the Constitutional Court. The history of the establishment of the Constitutional Court (MK) began with the adoption of the idea of a Constitutional Court in constitutional amendments. In the course of normative juridical arrangements regarding the Constitutional Court, there have been four amendments, namely (1) Law Number 24 of 2003 concerning the Constitutional Court; (2) Law Number 8 of 2011 concerning Amendment of Law Number 24 of 2003 concerning the Constitutional Court; and (3) Government Regulation in Lieu of Law Number 1 of 2013 concerning Second Amendment to Law Number 24 of 2003 concerning the Constitutional Court which has been ratified into law with Law Number 4 of 2014 and has been cancelled by MK Decision Number 1-2 / PUU-XII / 2014. This is due to several problems faced by the Constitutional Court, namely Constitutional Court Judges who violated the code of ethics to commit corruption and bribery. Of course, there is a need for a comprehensive study relating to (1) Appointment of Constitutional Justices and Panel of Experts and (2) External Oversight of Constitutional Justices and the Ethics Board of Constitutional Justices. use the Progressive Legal Theory approach to get solutions to the problematics that occur, which explore the values contained in society. In its arrangement, the Expert Panel and External Oversight have been regulated in Perppu No. 1 of 2013 which has been stipulated as Law Number 4 of 2014, but in that Act, the Court considers that the Expert Panel and External Oversight Committee formed by the Judicial Commission is considered unconstitutional because there is no principle of checks and balances within the judicial authority. With the susceptibility of constitutional judges to take actions outside of authority and other factors that have implications for the declining level of the Constitutional Court's confidence in society. Therefore, the researcher here wants to reconstruct a Panel of Experts and External Supervisors who answer the previous problems. The purpose of the Reconstruction of Panel of Experts and External Oversight is to realize a law enforcement system that is free of corruption, collusion, nepotism.